Suicidal patients in a psychiatric emergency unit: clinical characteristics and aggression profile - Vítor Crestani Calegaro; Cleonice Zatti; Andre Goettems Bastos; Lucia Helena Machado Freitas (Trends in Psychiatry and Psychotherapy, 2018)
Abstract Objective To explore and describe a profile of patients admitted to a psychiatric emergency facility, comparing patients with and without a recent suicide attempt in terms of their clinical characteristics and aggression. Methods This was an exploratory comparative study where patients were assessed using the Brief Psychiatric Rating Scale (BPRS) and the Overt Aggression Scale (OAS). Participants with a suicide attempt in the last 24 hours (SA) were compared to participants with a prior history of suicide attempt but no recent attempt (PHSA). Results 63 individuals (SA: 26; PHSA: 37) were selected. Both groups had similar demographic and clinical characteristics. The most prevalent diagnoses were mood (57.1%) and personality (50.8%) disorders. The majority of patients in both groups had a history of aggression episodes. Physical aggression in the week prior to admission was more prevalent in the PHSA group (51.4 vs. 19.2%, p = 0.017). The PHSA group also presented higher activation scores (p = 0.025), while the SA group presented higher affect scores on BPRS dimensions (p = 0.002). Conclusion The majority of individuals with a history of suicide attempt also presented a history of aggression. Inpatients with recent suicide attempt were hospitalized mainly due to the risk of suicide, while those with no recent suicide attempt were hospitalized mainly due to the risk of hetero-aggression. These findings support the hypothesis of an aggressive profile in suicidal patients and may open up a path for future research.